The struggle for europe : the turbulent history of a divided continent, 1945 to the present - Hitchcock, William I. 1965- (Anchor Books, 2004)
From the ashes of World War II to the conflict over Iraq, William Hitchcock examines the miraculous transformation of Europe from a deeply fractured land to a continent striving for stability, tolerance, democracy, and prosperity. Exploring the role of Cold War politics in Europe's peace settlement and the half century that followed, Hitchcock reveals how leaders such as Charles de Gaulle, Willy Brandt, and Margaret Thatcher balanced their nations' interests against the demands of the reigning superpowers, leading to great strides in economic and political unity. He re-creates Europeans' struggles with their troubling legacy of racial, ethnic, and national antagonism, and shows that while divisions persist, Europe stands on the threshold of changes that may profoundly shape the future of world affairs.